Comparative Study of 3D Conformal Radiation Therapy by 3 Fields v/s 5 Fields Treatment Planning Techniques for Head and Neck Cancer - Jakhar, Dharampal; Sihag, Rakesh Kumar; Saharan, Vidushi; Dhaka, Saroj; Beniwal, Surender; Jakhar, Shankar Lal (Asian Pacific Journal of Cancer Care, 2024)
Objective: This study aimed to compare conventional 3-field and 5-field treatment planning techniques during 3-dimensional conformal radiotherapy (3D-CRT) in terms of organ at risk (OAR) sparing, planning target volume (PTV) coverage, treatment response, and toxicities in head and neck cancer patients. Materials and methods: Fifty biopsy-proven and registered patients with head and neck cancer participated in this study. Patients were randomized into two arms: Arm A (3D-CRT using a 3-field delivery technique) and Arm B (3D-CRT using a 5-field delivery technique). All patients received radiation therapy on a linear accelerator with concurrent weekly cisplatin chemotherapy. Target volumes and normal structures were manually contoured on the axial slices of the planning CT scan. Patients were evaluated at the end of treatment and during follow-up visits at 1, 3, and 6 months. Results: At the end of treatment, complete response was achieved in 22 (88%) patients in Arm A and 23 (92%) patients in Arm B. At 6 months, complete response rates were 76% and 80% in Arms A and B, respectively (p-value = 0.6836). Grade 3 xerostomia occurred in 12% of patients in Arm A and 4% of patients in Arm B (p-value = 0.92). The mean V95 (percentage of PTV receiving at least 95% of the prescribed dose) was 90.93 for the conventional 3-field technique and 93.28 for the 5-field technique (p-value = 0.08). Conclusion: The 5-field 3D-CRT technique can effectively spare the parotid glands and other OARs while providing better PTV coverage, particularly in patients with laryngeal carcinoma, N2 or less nodal involvement, and no involvement of higher neck node levels.